Self-Employment out of Dissatisfaction: An International Study - Niels G. Noorderhaven; Sander Wennekers; Geert Hofstede; A. Roy Thurik; Ralph E. Wildeman (Tinbergen Institute, 1999)
This paper studies differences in the rate of self-employment (business ownership) in more thantwenty Western nations and Japan for the period 1974-1994, focusing in particular on theinfluences of dissatisfaction and uncertainty avoidance. We test two types of hypotheses, pertainingto the positive influence of various forms of dissatisfaction on the level of self-employment, and todifferences between the importance of various push and pull factors in low and high uncertaintyavoidance countries. The two types of hypotheses are related, as inhabitants of high-uncertaintyavoidance cultures tend to express lower levels of satisfaction with life. Using a longitudinaldataset covering 12 European countries, and controlling for important economic factors, we findthat dissatisfaction is a very important variable for explaining differences in self-employmentlevels. Dissatisfaction seems to be a factor promoting self-employment, not only at the level of theindividual, but also at the level of societies. Hofstede's Uncertainty Avoidance Index is used todistinguish between low and high-uncertainty avoidance countries, and the factors influencingselfemployment rates within these two clusters are investigated in a set of 23 countries. In the group ofhigh-uncertainty avoidance countries a strong negative relationship between GDP per capita andthe level of self-employment is found, in low-uncertainty avoidance countries the profits associatedwith being self-employed are a significant factor. These findings, which support the hypotheses,suggest that in high-uncertainty avoidance countries self-employment is often caused by a lack ofprosperity (a push factor); in low-uncertainty avoiding countries the pull factor of expected profitsis more important.
Keywords: 330; Selbstständige; Welt